VIBE: Evaluation of Ibandronate Efficacy - Original Investigation - J-Y Reginster; S Poston (Galenos Yayinevi, 2008)
No prospective head-to-head trials comparing the fracture efficacy of the currently marketed weekly and monthly bisphosphonates have been conducted. Due to the large sample size such studies would require to reliably detect differences in fracture risk and the associated high costs, they are considered to be impractical. Whilst providing the highest level of evidence, clinical trials also have inherent limitations. Patients are selected by a number of criteria and therefore usually do not represent the normal patient population. Also due to a protocol, normal clinical practice is usually not reflected. In contrast, database studies allow the assessment of treatments in normal clinical practice. Whilst observational studies have limitations owing to more confounding variables, they do have an important place in evidence-based medicine (especially in the absence of prospective clinical trials), and if well-designed can give some indications regarding the comparative efficacy of osteoporosis therapies in real-world clinical practice. (From the World of Osteoporosis 2008;14: 62-5)